2016
DOI: 10.1002/jcp.25617
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia Enhances Epithelial‐Mesenchymal Transition and Invasiveness, and Restrains the Warburg Phenotype, in Hypoxic HeLa Cell Cultures and Microspheroids

Abstract: The accelerated growth of solid tumors leads to episodes of both hypoxia and hypoglycemia (HH) affecting their intermediary metabolism, signal transduction, and transcriptional activity. A previous study showed that normoxia (20% O ) plus 24 h hypoglycemia (2.5 mM glucose) increased glycolytic flux whereas oxidative phosphorylation (OxPhos) was unchanged versus normoglycemia in HeLa cells. However, the simultaneous effect of HH on energy metabolism has not been yet examined. Therefore, the effect of hypoxia (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 96 publications
1
26
0
2
Order By: Relevance
“…It was recently shown that detachment of tumor cells from the ECM disrupts glucose metabolism and induces increased ROS species [ 100 ]. In agreement with this data, the formation and growth of MCTS is dependent on sufficient glucose availability and activation of antioxidant pathways [ 49 , 100 , 101 ]. To facilitate growth in MCTS and within hypoxic microenvironments, tumor cells activate signaling through HIF proteins [ 57 ].…”
Section: Introductionsupporting
confidence: 62%
“…It was recently shown that detachment of tumor cells from the ECM disrupts glucose metabolism and induces increased ROS species [ 100 ]. In agreement with this data, the formation and growth of MCTS is dependent on sufficient glucose availability and activation of antioxidant pathways [ 49 , 100 , 101 ]. To facilitate growth in MCTS and within hypoxic microenvironments, tumor cells activate signaling through HIF proteins [ 57 ].…”
Section: Introductionsupporting
confidence: 62%
“…Many cells die from these stressful conditions, but the survivors, undergoing dramatic shifts in redox status with mitochondrial and nuclear damage from ensuing oxidative stress, promote further malignancy and metastasis [6,9]. This selection pressure, promoted by the combined stressful conditions of hypoxia plus hypoglycaemia [10] involves dysfunctional mitochondrial ATP synthesis (i.e., oxidative phosphorylation; OxPhos), causing enhanced release of ROS as a by-product of an impaired respiratory chain, which then causes mutations, particularly in the adjacent susceptible mitochondrial DNA, and eventually enhances metastasis [11][12][13][14]. As a consequence, cytosolic Ca 2+ levels become elevated which helps trigger epithelialmesenchymal transition, accelerated growth and invasiveness together with the emergence of more highly metastatic cancer stem cells [15].…”
Section: Abstract: 230 Wordsmentioning
confidence: 99%
“…33,77,78 The tumor microenvironment during rapacious growth phases will concomitantly cause intermittent periods of hypoxia, [79][80][81] acidosis, 82,83 and nutrient deprivation resulting in hypoglycemia, all factors which consequently induce a major reprogramming of cancer cell metabolism. 46,47,[84][85][86][87][88][89] These microenvironmental stress related changes in cancer cell metabolism are frequently associated with greater ROS production. 90 1.4 | Switch in redox control from de novo GSH synthesis to NADPH from the PPP in advanced cancer cells One major mechanism for enhancing ROS levels in cancer cells occurs via a feedback amplification loop involving ROS-mediated increase in cytosolic NADPH production.…”
Section: Why the Mitochondrial Ros Production System Provides Novelmentioning
confidence: 99%
“…ROS production systems become elevated in more advanced stage cancer cells to promote their growth and survival . The tumor microenvironment during rapacious growth phases will concomitantly cause intermittent periods of hypoxia, acidosis, and nutrient deprivation resulting in hypoglycemia, all factors which consequently induce a major reprogramming of cancer cell metabolism . These microenvironmental stress related changes in cancer cell metabolism are frequently associated with greater ROS production …”
Section: Introductionmentioning
confidence: 99%